KONTROL LAMPU PADA GEDUNG BERTINGKAT BERBASIS PERSONAL COMPUTER (PC) - Aziz, Muh. Abdul (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2009)
Need of electricity energy on the building, industries and firms mount increase, if we can not solve this increasing, it can influence needs of national electricity energy. While the establishing of new electricity generator about 1,2 % in a year. This condition has to be perceived seriously by building constructor to convince the using of electricity energy by doing energy economical program. The purpose of this research is making a lamp control system on the building which can â€œonâ€ or â€œofâ€ the lamp by the electric swi tch in each of room and by program on PC. By doing this system, the lamp lamp controlling can be done easily, effective and efficient so that, it can economic electricity energy. This tool consists of two designs; they are mechanic design and electronic design. Mechanic design consists of room miniature, lamp which is connected with relay and Photodiode sensor. While electronic design consists of LM311, shift Register input, shift register output, ULN 2003 and DB 25. Then the tool is connected with PC through parallel port communication. This system is controlled by the main program on PC wich uses Delphi 7.0. Testing of sensor is done by looking for the tense is out from sensor when there is light and no light. While test of the whole tools by giving income (push) on the button/ the button on the program then look at the lamp output, whether it is match with incaome or not. From the testing result of the whole systems can be concluded that lamp control by using Delphi 7.0 can do wll. It shows same output to input given. If lamp is on, push the button on the program appearance. It will be yellow color and if lamp is broken or did not paired on the program button, it will be red color. Kata Kunci: Kontrol, Lampu, Personal Computer (PC)